The Effectiveness of Choral Reading Method Toword Reading Comprehension At Ninth Grade of SMP Plus Nurul Islam: English - Hana Syafira; Suhono; Rizky Hidayatullah (Journal of English Development, 2023)
The aims of this article was to know the effectiveness of choral reading method toward studentsreading comprehension. In this study, the researchers used quantitative research in the form ofquasi-experimental design by testing the pre-test and post-test. The samples were taken fromclass 9a and class 9b. The treatment was conducted for 3 meetings. The population of this studywere 9th grade students at SMP Plus Nurul Islam. Collecting the data used multiple choicequestions as an instrument. After the treatment, the instrument was used for pre-test and posttest. After being given the pre-test and post-test, the researchers used the SPSS to computeindependent T-test. In this study, researchers used quantitative research. Researchers used aquasi-experimental design by testing the pre-test and post-test. The result showed that choralreading method was effective toword students' reading comprehension at ninth grade of SMPPlus Nurul Islam. It can be seen from Sig. (2-tailed) of the equal variance assumed in theIndependent Samples test table where the Sig. (2-tailed) is 0.004. It is lower than α = 0.05 and itmeans that Ho is rejected and Ha is accepted.